Assessing exposure risks for freshwater tilapia species posed by mercury and methylmercury - Cheng, Yi-Hsien (Ecotoxicology (London, England), 2016)
Waterborne and dietborne exposures of freshwater fish to mercury (Hg) in the forms of inorganic (Hg(II)) and organic (methylmercury or MeHg) affect their growth, development, and reproduction. However, an integrated mechanistic risk model framework to predict the impact of Hg(II)/MeHg on freshwater fish is lacking. Here, we integrated biokinetic, physiological and biogeographic data to calibrate and then establish key risk indices-hazardous quotient and exceedance risk-for freshwater tilapia species across geographic ranges of several major rivers in Taiwan. We found that Hg(II) burden was highest in kidney followed by gill, intestine, liver, blood, and muscle. Our results showed that Hg was less likely to pose mortality risk (mortality rate less than 5 %) for freshwater tilapia species. However, Hg is likely to pose the potential hazard to aquatic environments constrained by safety levels for aquatic organisms. Sensitivity analysis showed that amount of Hg accumulated in tilapia was most influenced by sediment uptake rate. Our approach opens up new possibilities for predicting future fish population health with the impacts of continued Hg exposure to provide information on which fish are deemed safe for human consumption